Sedum simingshanense (Crassulaceae), a new species from Zhejiang, East China - Shi-Qi She; Yang Zhang; Xin Zhou; Ya-Jun Peng; Shen-Hao Yao; Xing-Xing Zhao; Jia Yang; Yue-Liang Xu (PhytoKeys)
In this paper, Sedum simingshanense sp. nov. is described as a new species based on morphological and molecular analyses, and its taxonomic relationships are discussed. Morphological analysis indicates S. simingshanense should be classified in the genus Sedum sect. Sedum and is distinct from the related species S. xunvense and S. formosanum in the morphology of its solitary, light green and smooth stems, flattened leaves, larger, obovate and spurless sepals, yellow anthers, 22–30 ovules per carpel, oblique follicles, and its habitat on shaded slopes or rocks. Phylogenetic analysis of sequences of the nuclear ribosomal internal transcribed spacer (ITS) also demonstrates that S. simingshanense has a highest similarity of only 97.22% with any known species and S. formosanum is the closest extant relative of the new species.